If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x=2/3x-13
We move all terms to the left:
5x-(2/3x-13)=0
Domain of the equation: 3x-13)!=0We get rid of parentheses
x∈R
5x-2/3x+13=0
We multiply all the terms by the denominator
5x*3x+13*3x-2=0
Wy multiply elements
15x^2+39x-2=0
a = 15; b = 39; c = -2;
Δ = b2-4ac
Δ = 392-4·15·(-2)
Δ = 1641
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(39)-\sqrt{1641}}{2*15}=\frac{-39-\sqrt{1641}}{30} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(39)+\sqrt{1641}}{2*15}=\frac{-39+\sqrt{1641}}{30} $
| 3x-x=-21 | | 291=10-x | | (5x^2-18x-27)/(x-5)=0 | | 10+2x=7x-25 | | x=1/3(3x)-8 | | -3z-9=(5z-4) | | 2x+(x-1)=-4 | | (-5x)+3x=32 | | -4/3+6/7v=-1/2 | | 2x+24=1/2x | | 75+14m=173 | | 21n-30=285 | | 98=174-y | | 35=-y+293 | | 11x=87 | | –18+3x=–3 | | 4y(4-1)=12 | | 13x-3(3x-3)=3x+6 | | (4s-6)^2=0 | | 3/4(8-2y)=3 | | p/32/3=2/3 | | x-69/10=3/10 | | 5+5-3x=40 | | 12x+15=49 | | 5/230/11=t | | -6=y+3/5 | | 3/4=w/9 | | 4c=8/11 | | (2x+4)^2=144 | | 4t=1/2 | | 2(20-x)+3=180 | | 2x^2+3x-185=0 |